Bioecology Study of Brackish Pond Waters for Saline Tilapia in Petta Barat Village Sangihe Archipelago District - Febertin T. Sondak; Asriani E. Medellu; Ersa K. N. Legrants; Delfian F. Koneng; Magdalin Ulaan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Problems that often arise in the fisheries sector, especially in the development of saline tilapia aquaculture, are always related to constraints in feed supply. Therefore, feed management involving the use of immunostimulants is required as an effort to improve the growth and survival of saline tilapia. Thus, the objective of this study was to identify the relationship between the use of immunostimulant yeast derived from natural extracts of cucumber fruit on the relative growth rate of saline tilapia and its relationship with ecological characteristics and water quality in saline tilapia ponds in Petta Barat Village, Sangihe Regency. This study applied a completely randomized experimental design (CRED) with four treatment groups and repeated it three times. The treatment groups were A (no addition of natural yeast in feed), B (10 ml natural yeast/kg feed), C (20 ml natural yeast/kg feed), and D (30 ml natural yeast/kg feed). Feeding was done twice a day, with the amount of feed given as 5% of the fish body weight. The findings of this study indicated that variations in the addition of natural yeast of cucumber fruit extract to the feed did not result in a significant impact on the relative growth rate of saline tilapia. In addition, water quality parameters such as temperature, pH, dissolved oxygen (DO), salinity, nitrate, nitrite, and ammonia remained within appropriate ranges and supported the survival of saline tilapia.